Rewriting the Mothers in Joyce’s Dubliners for the 21st Century: Oona Frawley’s “The Boarding House” and Elske Rahill’s “A Mother” - Anténe, Petr (American & British Studies Annual, 2025)
Within the multifaceted portrayals of the people in James Joyce’s seminal short story collection Dubliners (1914), a complex and not particularly positive portrayal of motherhood emerges, as the mothers attempt to support their children in ways that may appear rather problematic. For example, in “The Boarding House,” Mrs Mooney manoeuvres the well-off Mr Doran into an affair and, consequently, a wedding with her daughter, knowing he will be careful not to harm his reputation. Similarly, in “A Mother,” Mrs Kearney attempts to use the Irish Revival to improve her family’s social standing by arranging for her daughter Kathleen to be hired as an accompanist for four concerts, and then later insists on Kathleen being paid all the promised money regardless of the changing circumstances. In 2014, the collection Dubliners 100: Fifteen New Stories Inspired by the Original was published, with each story set in the early twenty-first century and adapted by a different contemporary Irish writer. This article thus aims to show how two women writers, Oona Frawley and Elske Rahill, rewrite and update Joyce’s portrayal of Irish motherhood in their versions of “The Boarding House” and “A Mother.”